Kisspeptin antagonist prevents RF9-induced reproductive changes in female rats - Sahin, Zafer; Canpolat, Sinan; Ozcan, Mete; Ozgocer, Tuba; Kelestimur, Haluk (Bioscientifica Ltd, 2015)
The aim of this study was to determine the modulatory effects of peptide 234 (p234) (an antagonist of GPR54 receptors) on kisspeptin and RF9 (an RFamide-related peptide antagonist)-induced changes in reproductive functions and energy balance in female rats. Female Sprague-Dawley rats were weaned on postnatal day (pnd) 21. The animals were intracerebroventricularly cannulated under general anesthesia on pnd 23. Groups of female rats were injected with kisspeptin, RF9, p234, kisspeptin plus p234, or RF9 plus p234, daily. The experiments were ended on the day of first diestrus following pnd 60. Kisspeptin or RF9 alone advanced vaginal opening (VO), which was delayed by administration of kisspeptin antagonist alone. In the rats given kisspeptin plus p234 or RF9 plus p234, VO was not different from control rats. Kisspeptin and RF9 elicited significant elevations in circulating LH levels. Coadministrations of kisspeptin or RF9 with p234 decreased LH levels significantly. The use of p234 alone did not cause any significant change in LH secretion. Kisspeptin decreased both food intake and body weight while RF9 decreased only food intake without affecting body weight. The effects of kisspeptin on energy balance were also reversed by central administration of p234. In conclusion, kisspeptin antagonist, p234, modulates the effects of kisspeptin on reproductive functions and energy balance, whereas RF9 seems to exert only its effects on reproductive functions by means of GPR54 signaling in female rats.
Keywords: Protein-Coupled Receptor; Amide-Related Peptides; Hormone Neurons; Neuropeptide-Y; Food-Intake; Adult Male; Gonadotropin; Expression; Secretion; System